Community health worker motivation to perform systematic household contact tuberculosis investigation in a high burden metropolitan district in South Africa - Gladys Kigozi; Christo Heunis; Michelle Engelbrecht (BMC, 2020)
Abstract Background South Africa faces a chronic shortage of professional health workers. Accordingly, community health workers (CHWs) are being employed to mitigate the ongoing health workforce deficiencies. As increased access to quality service delivery hinges upon their motivation, this study explored CHWs' motivation to deliver systematic household contact tuberculosis (TB) investigation (SHCI). Methods In 2017, a cross-sectional survey was conducted among CHWs in the Mangaung Metropolitan District, Free State Province. Exploratory factor analysis was performed on a 30-item scale to determine the dimensions underlying CHW motivation. Items with factor loadings of 0.4 and above were retained. Descriptive and inferential analyses were used to determine CHW motivation levels. Multiple linear regression analysis was used to investigate the determinants of CHW motivation. Results Out of 235 participants, 89.2% were female. Participants' median age was 39 (inter-quartile range: 33-45) years. CHW motivation was defined by 16 items across three dimensions - intrinsic job satisfaction, burnout and team commitment, together explaining 56.04% of the total variance. The derived scale showed satisfactory internal consistency (Cronbach's alpha: 0.81), with a mean motivation score of 52.26 (standard deviation [sd]: 5.86) out of 64. Statistically significant differences were observed between formal CHWs - those with at least phase 1 standardised accredited training, and informal CHWs - those without such accredited training regarding team commitment scores (17.82 [sd: 2.48] vs. 17.07 [sd: 2.82]; t (233) = 2.157; p = 0.013). CHW age (β = 0.118, p = 0.029), location (β = 1.737, p = 0.041), length of service (β = − 0.495, p < 0.001), attendance of TB SHCI training (β = 1.809, p = 0.036), and TB SHCI competence (β = 0.706, p < 0.001), contributed statistically significantly to CHW motivation. Conclusion CHW motivation to perform TB SHCI was both intrinsic and extrinsic. The high overall mean score implies that the CHWs were well-motivated to perform TB SHCI. To ensure sustained improved access to quality TB SHCI service provision, programme managers in the Free State and similar settings could potentially use the tool derived from this study to monitor and inform CHW motivation interventions. Interventions should pay close attention to the CHWs' formalisation, competence and training.